Health literacy correlates with abbreviated full‐scale IQ in adolescent and young adults with sickle cell disease. Issue 5 (2nd March 2023) - Bhatt, Nidhi; Calhoun, Cecelia; Longoria, Jennifer; Nwosu, Chinonyelum; Howell, Kristen E.; Varughese, Taniya; Kang, Guolian; Jacola, Lisa M.; Hankins, Jane S.; King, Allison
Abstract: Introduction: Sickle cell disease (SCD) is a chronic condition with progressive neurocognitive deficits. Health literacy (HL) is essential during adolescence and young adulthood, as the transition to adult care requires healthcare decisions. HL is known to be low in SCD; however, relation between general cognitive ability and HL has not been investigated. Methods: This cross‐sectional study included adolescent and yound adults (AYAs) with SCD from two institutions. Logistic regression measured the association between HL, measured by the Newest Vital Sign tool, and general cognitive ability, measured with abbreviated full‐scale intelligence quotient (FSIQ) on the Wechsler Abbreviated Scale of Intelligence. Results: Our cohort contained 93 participants at two sites: 47 (51%) at Memphis, TN and 46 (49%) at St. Louis, MO, ranging from ages 15–45 years (mean = 21 years) and with a majority (70%) possessing a high school education or greater. Only 40/93 participants (43%) had adequate HL. Lower abbreviated FSIQ ( p  < .0001) and younger age at assessment ( p  = .0003) were associated with inadequate HL. For every standard score point increase in abbreviated FSIQ, the odds of having adequate HL compared to limited or possibly limited HL increase by 1.142 (95% confidence interval [CI]: 1.019–1.322) and 1.116 (95% CI: 1.045–1.209), respectively, after adjusting for age, institution, income, and educational attainment. Conclusions: Understanding and addressing HL is imperative in improving self‐management and health outcomes. Among AYA with SCD, low HL was prevalent and influenced by abbreviated FSIQ. Routine screening for neurocognitive deficits and HL should be performed to guide development of interventions to adapt to the HL of AYA with SCD.